CO2 quality control through scrubbing in oxy-fuel combustion: Rate limitation due to S(IV) oxidation in sodium solutions in scrubbers and prior to waste disposal. (August 2015) - Liu, Dunyu; Wall, Terry; Stanger, Rohan
Highlights: Oxidation of S(IV) was studied in two types of reactors. The dependence of oxidation rate of S(IV) on pH was obtained. Oxidation rate of S(IV) in the WSR was liquid mass transfer controlled. Waste sodium solutions maybe neutralized prior to disposal. Abstract: Oxy-fuel combustion is a promising CCS technology which is being demonstrated prior to commercialization. While the flue gas in oxy-fuel combustion is concentrated in CO2, it contains impurities such as SO2 . The reduction of SO2 prior to compression by a scrubber is a common feature of oxy-fuel systems. These scrubbers use sodium solutions. The products of the sodium-based scrubber after capture of SO2 contain Na2 SO3 and NaHSO3 . In the presence of O2 in the gas phase, sulphur related species (i.e., SO3 2− and HSO3 − ) in liquid phase will be irreversibly oxidized to sulphate. These sulphur related species are noted as S(IV). The oxidation of S(IV) could vary along the height of a spray tower due to changes in pH. The study of the S(IV) oxidation rate at different pH is helpful in evaluating the oxidation extent of S(IV) and understanding the impacts of S(IV) on the absorption rate of SO2 . Both the heterogeneous oxidation and the homogeneous oxidation of S(IV) were studied here using two types of experimental reactors (Gas liquid reactor and liquid reactor). Heterogeneous experiments were conducted in the gas liquid reactor. In experiments, liquid phase pH and exit SO2 were recorded continuously. Liquids were also taken for sulphate analysis after certain time period (30–60 min). For homogenous experiments, pH was monitored continuously and dissolved oxygen (DO) levels were manually recorded. For the heterogeneous oxidation, the oxidation of S(IV) results in reduction in pH, at pH 5.48, SO2 starts to be desorbed. With this reduction in pH, the oxidation rate of S(IV) changes accordingly. The oxidation of 0.01 M S(IV) stays stable at pH > 5.48. The oxidation rate of S(IV) drops by 44.5% at pH < 5.48. For the homogeneous oxidation, there are three regions of oxidation rate. In region 1 (i.e., pH > 5.6), the oxidation rate of S(IV) does not change with pH; in region 2 (i.e., 4.53 < pH < 5.6), the oxidation rate of S(IV) decreases dramatically with the decrease in pH. The oxidation rate of S(IV) at pH 4.53 is two magnitudes lower than the rate at the pH 5.6. In region 3 (i.e., pH < 4.53), the oxidation rate of S(IV) does not seem to change. The oxidation of S(IV) is presumably due to the oxidation of SO3 2− . Comparisons between heterogeneous and homogeneous oxidation indicate that the heterogeneous oxidation rate of S(IV) at pH > 5.48 is located in the liquid phase mass transfer controlled region. Below pH 5.48, the heterogeneous oxidation rate of S(IV) does not drop as much as homogeneous oxidation rate. This is possibly because the heterogeneous oxidation rate of S(IV) is enhanced by desorption of SO2 to produce SO3 2− for oxidation. Results have implications on the disposal of waste sodium solutions after absorption. The oxidation of S(IV) in discharged solutions results in a final pH of about 4 which may be neutralized to form Na2 SO3 prior to disposal.